STRATEGI PENGEMBANGAN FASILITAS REKREASI OBJEK WISATA DANAU DIATAS KABUPATEN SOLOK SUMATERA BARAT - Novendra, Riki; Yuliana, Yuliana; Pasaribu, Pasaribu (Journal of Home Economics and Tourism, 2016)
The purpose of this study was to determine the development strategy (strength, weaknesses, opportunities, treats) Recreational facilities (outdoor) Attraction above Solok regency of West Sumatra future. This research is a descriptive study with qualitative data. Data was collected using interviews, observation, and documentation involving informants using Snowball Sampling technique, that is: Attraction manager above, attractions surrounding communities, as well as tourists. The results of this study show that: 1). The strength or carrying capacity of recreational facilities (outdoor) Lake Above attraction is has a large area, a beautiful natural scenery, cool and pristine, a strategic place that is easily accessible, abundant water resources of the lake. 2). The disadvantage is the limited local government budget, the lack of assistance from the government, the lack of professional workforce, yet their investors, the lack of maintenance of existing recreational facilities. 3). Chances are their outside investors, increasing tourist arrivals, the cooperation of local governments and the central government, the cooperation of immigrants and native son. 4). The threat is a discrepancy with custom behavior style diners around, traveler awareness to keep the attraction, Attraction competition alike, the development of other tourist attractions. The development strategy of recreational facilities (outdoor) Attractions Lake Above Solok regency of West Sumatra are: 1). Utilizing the natural potential to increase the number of tourist visits. 2). Boosting cooperation between local government, Central government, nomads, sons of the soil, 3) Developing and providing recreational facilities (outdoor). 4). Increase potentials owned attraction above the lake so as not to lose competitiveness with surrounding attractions. 5). Incentive to find investors and raise funds from both private and related institutions. 6. Develop and allocates the budget for the development of recreational facilities attraction above lake.Keywords: Strategy, Development, Recreation Facilities.